183 GHz Water Megamasers in Active Galactic Nuclei: A New Accretion Disk Tracer - Dominic W. Pesce; James A. Braatz; Christian Henkel; Elizabeth M. L. Humphreys; C. M. Violette Impellizzeri; Cheng-Yu Kuo (The Astrophysical Journal, 2023)
We present the results of an Atacama Large Millimeter/submillimeter Array survey to identify 183 GHz H _2 O maser emission from active galactic nuclei (AGNs) already known to host 22 GHz megamaser systems. Out of 20 sources observed, we detect significant 183 GHz maser emission from 13; this survey thus increases the number of AGN known to host (sub)millimeter megamasers by a factor of 5. We find that the 183 GHz emission is systematically fainter than the 22 GHz emission from the same targets, with typical flux densities being roughly an order of magnitude lower at 183 GHz than at 22 GHz. However, the isotropic luminosities of the detected 183 GHz sources are comparable to their 22 GHz values. For two of our sources—ESO 269-G012 and the Circinus galaxy—we detect rich 183 GHz spectral structure containing multiple line complexes. The 183 GHz spectrum of ESO 269-G012 exhibits the triple-peaked structure characteristic of an edge-on AGN disk system. The Circinus galaxy contains the strongest 183 GHz emission detected in our sample, peaking at a flux density of nearly 5 Jy. The high signal-to-noise ratios achieved by these strong lines enable a coarse mapping of the 183 GHz maser system, in which the masers appear to be distributed similarly to those seen in VLBI maps of the 22 GHz system in the same galaxy and may be tracing the circumnuclear accretion disk at larger orbital radii than the 22 GHz masers. This newly identified population of AGN disk megamasers presents a motivation for developing VLBI capabilities at 183 GHz.